Isolated Nerve Sheath Tumor Of Jejunum Presenting As Acute Abdomen (Bangladesh Journal of Medical Science, 2013)
Nerve sheath tumors of gastrointestinal tract are rare and occurs more frequently as systemic manifestations of generalized neurofibromatosis type-1(NF-1). In neurofibromatosis-1 lesions may be scattered or solitary tumor. Occasionally, such tumors may be the initial presenting feature of NF-1. Rarely, cases of isolated nerve sheath tumor of small intestine presenting with bleeding and obstruction have been documented. We report a 19years male presenting with nerve sheath tumor of jejunum in acute abdomen. His investigations show no features of NF-1. DOI: http://dx.doi.org/10.3329/bjms.v12i1.11754 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.91-92